2019
DOI: 10.1371/journal.pone.0225186
|View full text |Cite
|
Sign up to set email alerts
|

Mineral absorption is an enriched pathway in a brain region of restless legs syndrome patients with reduced MEIS1 expression

Abstract: Restless legs syndrome is a common complex disorder with different genetic and environmental risk factors. Here we used human cell lines to conduct an RNA-Seq study and observed how the gene showing the most significant association with RLS, MEIS1, acts as a regulator of the expression of many other genes. Some of the genes affected by its expression level are linked to pathways previously reported to be associated with RLS. We found that in cells where MEIS1 expression was either increased or prevented, miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…It has been proposed that HMOX1 is involved in brain aging and neurodegeneration [29], an observation which might be relevant to RLS considering that a small association has been reported to exist between this gene and RLS in a Spanish cohort [35]. HMOX1 has also been reported to be downstream of MEIS1 transcription factor [30]. It is noteworthy that we also observed a positive regulatory role of MEIS1 over SKOR1 in our earlier publication [8].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It has been proposed that HMOX1 is involved in brain aging and neurodegeneration [29], an observation which might be relevant to RLS considering that a small association has been reported to exist between this gene and RLS in a Spanish cohort [35]. HMOX1 has also been reported to be downstream of MEIS1 transcription factor [30]. It is noteworthy that we also observed a positive regulatory role of MEIS1 over SKOR1 in our earlier publication [8].…”
Section: Discussionsupporting
confidence: 72%
“…This gene has been suggested to play roles in brain aging and neurodegeneration [29]. In a recent publication our group also reported HMOX1 to be part of the MEIS1 regulatory network (MEIS1 has a positive regulatory role on HMOX1 expression) [30]. In addition to ferroptosis, other pathways were also found to be significantly enriched in the genes possibly activated by SKOR1 (Table 2).…”
Section: Pathway and Gene Set Enrichment Analysis Shows Pathways Related To Known Rls Mechanismsmentioning
confidence: 85%
“…Minerals were fundamental nutrients and mineral absorption may depend on dietary ingredient composition. Some genes in “mineral absorption pathway” were involved in iron metabolism [ 69 , 70 ]. These could explain why they were all identified and suggest that ferroptosis may be the key pathway involved in fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…MTs are highly relevant to RLS as they bind intracellular metals, protect against oxidative stress and interact with ferritins which manage iron level in the central nervous system. While MTs have been implicated in the pathogenesis of neurodegenerative diseases such as Parkinson's disease this was the irst study showed the molecular association with RLS [61,62].…”
Section: Restless Legs Syndrome (Rls)mentioning
confidence: 99%